Psychological Needs Satisfaction and Thwarting, Burnout, and Controlling Coach Behaviors among Athletes: A Structural Model on Team Climate - Arianne Michael Sim Monderondo Tuano; Arvin Alcaraz Andacao; Jovelito Dora (Journal of Coaching and Sports Science, 2025)
Background: Team climate plays a crucial role in athletes' psychological well-being and performance. While sports participation fosters social connections and mental wellness, athletes also face stressors that impact their motivation and well-being.Aims: This study aimed to assess the levels of psychological needs satisfaction (PNS), psychological need thwarting (PNT), burnout (BO), controlling coach behavior (CCB), and team climate (TC) among athletes. It also examined the relationships among these variables, identified key predictors of team climate, and determined the best-fitting model explaining team climate in a sports context.Methods: A descriptive-correlational design and Structural Equation Modeling (SEM) were used to analyze data from 57 competitive athletes. PNS, PNT, CCB, and BO were measured to identify key predictors influencing TC and its model parsimony.Results: Mean scores indicated moderate to high levels of PNS (x̄=5.87), PT (x̄=3.30), BO (x̄=3.00), CCB (x̄=2.90), and TC (x̄=5.53). Correlation analysis revealed that PNS positively correlated with TC (r=0.545; p<0.01), while PT (r=-0.362; p<0.01) and BO (r=-0.200; p<0.05) negatively correlated with TC. Multiple regression showed that PNS (β=0.626; p=0.000), PT (β=-0.504; p=0.000), and BO (β=0.423; p=0.004) significantly predicted TC, with an R² of 0.505. Among of the generated models, hypothesized model 4 met the high threshold indices (CMIN/DF=1.102, RMSEA=0.02, GFI=0.981, CFI=0.958, TLI=0.972, NFI=0.956).Conclusion: PNS emerged as the strongest predictor of TC, while PNT hindered it. Surprisingly, BO positively influenced TC, suggesting shared adversity may strengthen cohesion. CCB did not directly predict TC but indirectly influenced BO. The findings highlight the importance of athlete-centered coaching in fostering supportive teams and well-being.